NIMG-56. A MULTIMODAL 7 TELSA MRI INVESTIGATION OF LONG-TERM EFFECTS OF RADIOTHERAPY ON THE ADOLESCENT BRAIN & COGNITION. (11th November 2019) - Morrison, Melanie; Avadiappan, Sivakami; Yuan, Justin; Stoller, Schuyler; Jakary, Angela; Mueller, Sabine; Molinaro, Annette; Banerjee, Anu; Hess, Christopher; Braunstein, Steve; Lupo, Janine
Abstract: INTRODUCTION: Radiation therapy (RT) remains an integral role in the treatment of adolescent brain tumors, despite evidence of its long-term effects including cognitive impairment, vascular injury and reduced white matter integrity. While prior studies have related vascular injury to cognitive decline and associated more severe cognitive impairment with a whole-brain versus a focal RT approach, the relationship between underlying imaging, clinical, and treatment parameters has yet to be explored in this population. In this study we used multimodal 7 Tesla MR imaging to probe RT-induced changes in the brain and identified risk factors for clinical outcome. METHODS: Twenty-three patients (age 6–25 years) with non-supratentorial tumors treated with RT as children and 4 nonirradiated control patients (ages 13–16 years) were scanned on a 7T MRI system; eight patients underwent serial imaging 0.9–3.7 years following the first scan. Simultaneous MR-veniography and angiography, and 90-direction, dual-shell multi-band diffusion MRI were used to assess the relationships among cerebral microbleed (CMB) development, changes in arterial radii, and whole-brain white matter connectivity. A computerized cognitive battery (Cogstate) evaluated multiple domains of cognitive function. Multiple univariate and multivariate regression models with multiple comparison corrections identified risk factors. RESULTS: Cognitive status measured via executive function and working memory tasks revealed the strongest associations with type of RT and imaging parameters. Specific risk factors for worse outcome included whole-brain RT, RT at a younger age, and time since RT. On imaging this corresponded to increased CMB burden, decreased arterial volume, and reduced global structural connectivity; intrasubject serial imaging followed these trends. CONCLUSION: 7T-MRI was highly sensitive to CMBs with cumulative incidence rates greatly exceeding prior 3T studies in this population. This work demonstrates the value of multimodal 7T-MRI in providing metrics that reflect cognitive deficits arising from RT and identifying patients who would benefit the most from cognitive rehabilitation.